Prevention of arthrofibrosis during knee repair by extracorporeal shock wave therapy : preliminary study in rabbits - Zhou, Yufeng (2021)
Surgery or trauma may induce extensive arthrofibrosis around joints and tendon for the restrictive range of motion. Although some approaches were proposed, this problem is not solved satisfactorily. Extracorporeal shock wave therapy (ESWT) has been used for orthopedic, musculoskeletal, and fibrotic disorders. Whether it could prevent the formation of arthrofibrosis during the joint repair is unknown.